4х + 5 = 2х + 3(5х + 6)
4. 25 – 4(4х – 3) = 3(5х + 2)
5. 7х – 2(5х – 3) – 4(2 – 3х) = 1
6. 9(2x – 1) + 2 = 2(9x – 3) – 1
7. 7х + 5 = 5х + 7
8. 4х = 4 + 2(3х + 5)
9. 4(2х – 5) – х = 3х + 8
10. 7(3х – 2) – 6(4х + 7) = 18х
Ответы
Ответ:
Пошаговое объяснение:
4х + 5 = 2х + 3(5х + 6)
4x + 5 = 2x + 15x + 18
4x + 5 = 17x + 18
17x - 4x = 5 - 18
13x = -13
x = -1
4. 25 – 4(4х – 3) = 3(5х + 2)
25 - 16x + 12 = 15x + 6
37 - 16x = 15x + 6
15x + 16x = 37 - 6
31x = 31
x = 1
5. 7х – 2(5х – 3) – 4(2 – 3х) = 1
7x - 10x + 6 - 8 + 12x = 1
9x - 2 = 1
9x = 1 + 2
9x = 3
x = 3 : 9
x = 1/3
6. 9(2x – 1) + 2 = 2(9x – 3) – 1
18x - 9 + 2 = 18x - 6 - 1
18x - 7 = 18x - 7
18x - 18x = 7 - 7
0 = 0
x є (-∞ ; ∞)
уравнение имеет множество решений
7. 7х + 5 = 5х + 7
7x - 5x = 7 - 5
2x = 2
x = 1
8. 4х = 4 + 2(3х + 5)
4x = 4 + 6x + 10
4x = 14 + 6x
6x - 4x = -14
2x = -14
x = -14:2
x = -7
9. 4(2х – 5) – х = 3х + 8
8x - 20 - x = 3x + 8
7x - 20 = 3x + 8
7x - 3x = 20 + 8
4x = 28
x = 28 : 4
x = 7
10. 7(3х – 2) – 6(4х + 7) = 18х
21x - 14 - 24x - 42 = 18x
-3x - 56 = 18x
18x + 3x = -56
21x = -56
x = -56 : 21
x = -2 14/21
x = -2 2/3